Isolation of indigenous Glutathione producing Saccharomyces cerevisiae strains - Tahereh Tahmasebi; Rahim Nosrati; Hamed Zare; Horieh Saderi; Reyhaneh Moradi; Parviz Owlia (Iranian Society of Pathology, 2016)
Background: Glutathione (GSH) is a non-protein thiol compound, which plays an important role in the response to oxidative stress and nutritional stress. The aim of this study was to isolate indigenous S. cerevisiae strains capable of effectively produce GSH. Methods: One hundred-twenty sweet fruit samples were collected. The strains were isolated on yeast glucose chloramphenicol (YGC) agar medium and identified. The isolates were evaluated for GSH producing on yeast malt (YM) medium. Concentration of glutathione was investigated by recording absorbance of all samples at wavelength 412 nm (Ellman's method). In addition, optimization of glucose and peptone concentration in culture medium and the effects of various environmental conditions such as temperature (20-35 °C), agitation rate (150-250 rpm), and initial pH (4.0-6.0) were assessed on producing of GSH. Results: From 120 samples, 80 isolates were identified by morphological, biochemical and molecular tests as S. cerevisiae. Five isolates were capable to produce effectively GSH. The optimal culture conditions were agitation rate, 200 rpm; temperature, 30 °C; initial pH, 6; glucose, 30 g/l; and peptone concentration, 5 g/l. In optimal conditions, the amount of derived glutathione was improved compared to YM basal medium and highest GSH concentration (296.8 mg/l) was obtained after cultivation with shaking for 72 h. Conclusion: The possibility of obtaining S. cerevisiae cells with a high GSH intracellular content can be considered an interesting opportunity of furthering the range of application and utilization of this molecule.